2018
DOI: 10.23822/eurannaci.1764-1489.34
|View full text |Cite
|
Sign up to set email alerts
|

Cypress pollen allergy is responsible for two distinct phenotypes of allergic rhinitis different from other pollinosis

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…An exception to this rule was observed in Marseille, where many patients also reported moderate to severe symptoms although mono‐sensitized to cypress pollen. This may indicate a more severe clinical phenotype of cypress pollen allergy, also suggested by a younger age at disease onset (average 10 years) than observed in a previous local study 25 . Second, the frequency of comorbidities was also highly heterogeneous among study centers.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…An exception to this rule was observed in Marseille, where many patients also reported moderate to severe symptoms although mono‐sensitized to cypress pollen. This may indicate a more severe clinical phenotype of cypress pollen allergy, also suggested by a younger age at disease onset (average 10 years) than observed in a previous local study 25 . Second, the frequency of comorbidities was also highly heterogeneous among study centers.…”
Section: Discussionmentioning
confidence: 71%
“…This may indicate a more severe clinical phenotype of cypress pollen allergy, also suggested by a younger age at disease onset (average 10 years) than observed in a previous local study. 25 Second, the frequency of comorbidities was also highly heterogeneous among study centers. The highest number of comorbidities per patient was observed in Rome, which was also the center with the highest degree of poly-sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Leila et al found higher habitual snoring frequencies among children residing in neighborhoods with the highest pollution levels showed an inverse relationship between ambient air quality and snoring in school-aged children [ 27 ]. Particulate matter (PM 2.5 and PM 10 ) and pollen can penetrate deep into human lungs, resulting in biological changes in the respiratory system, including the induction of inflammatory reactions, oxidative stress, and DNA damage, which could exacerbate the symptoms of respiratory diseases such as asthma, sleep apnea, and rhinitis [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…L'allergie aux GRP se manifeste habituellement par un syndrome oral lors de l'ingestion du fruit incriminé (en été) avec prurit et angio-oedème, en plus des symptômes provoqués par l'inhalation du pollen de cyprès (en hiver) qui comprennent en plus de la rhinite, une toux sèche associée à une hyperréactivité bronchique chez un tiers des patients environ [39]. Des cofacteurs tels que l'activité physique ou la prise d'anti-inflammatoire non stéroïdien peuvent aggraver les symptômes jusqu'au choc anaphylactique [40,41].…”
unclassified